Air ambulance services in the Arctic 1999-2009 : a Norwegian study. - Norum, Jan; Elsbak, Trond M (International Journal of Emergency Medicine, 2011)
Air ambulance services in the Arctic have to deal with remote locations, long distances, rough weather conditions and seasonable darkness. Despite these challenges, the people living in the area expect a high quality of specialist health care. The objective of this study was to analyse the air ambulance operations performed in the Norwegian Arctic and study variations in diagnoses and flight patterns around the year. A retrospective analysis. All air ambulance operations performed during the time 1999 – 2009 period were analysed. The subjects were patients transported and flights performed. The primary outcome measures were patients’ diagnoses and task patterns around the year. A total of 345 patients were transported and 321 flights performed. Coronary heart and vascular disease, bone fractures and infections were the most common diagnoses. Most patients (85%) had NACA score 3 or 4. Half of all fractures occurred in April and August. Most patients were males (66%), and one fourth was not Norwegian. The median flying time (one way) was 3 h 33 m. Ten percent of the flights were delayed, and only 14% were performed between midnight and 8.00 AM. The period April to August was the busiest one (58% of operations). Norway has run a safe air ambulance service in the Arctic for the last 11 years. In the future more shipping and polar adventure operations may influence the need for air ambulances, especially during summer and autumn.